(untitled) (Philological Studies, 2019)
Georgi Trajchev (1869-1945) was a prominent educator, writer and publicist from Macedonia. He was the author of numerous articles published in newspapers and magazines of that period. He founded „Macedonian library“ in which he published 13 books with scientific research and travel literature features. Some of his works are the main source for the history of the western parts of Macedonia.